AB0919 H-Ferritin and CD68+/H-ferritin+ Cells Are Increased in The Skin of Adult Onset Still's Disease Patients and Correlate with The Disease Activity. (15th July 2016) - Ruscitti, P.; Cipriani, P.; Ciccia, F.; Di Benedetto, P.; Liakouli, V.; Berardicurti, O.; Carubbi, F.; Guggino, G.; Di Bartolomeo, S.; Triolo, G.; Giacomelli, R.
Abstract : Background: Adult onset Still's disease (AOSD) is an inflammatory disease, characterized by high spiking fevers, arthritis, salmon-pink erythema and multivisceral involvement [1]. During AOSD, exceptionally high serum levels of ferritin may be observed and they might contribute to production of proinflammatory molecules [2]. Ferritin is composed by 24 subunits, heavy (H) subunits and light (L) subunits. The ferritin enriched in L subunits (L-ferritin) and the ferritin enriched in H subunits (H-ferritin) may be recognized in different tissues [3]. Objectives: To investigate the skin tissue expression of both H-and L-ferritin and the number of macrophages expressing these molecules, in the inflammatory cutaneous infiltrate from 10 AOSD patients with persistent (more than 24–36 hours) cutaneous lesions. In addition, we performed statistical analysis to evaluate whether these results might correlate with the severity of the disease. Methods: We obtained skin samples from 10 consecutive patients with active AOSD with persistent cutaneous lesions and 10 healthy controls (HC). An immunofluorescence analysis was performed evaluating the tissue expression of both H- and L-ferritin and the number of macrophages expressing these moleculkes. Serum levels of ferritin, ESR, CRP, Pouchot's score were also recorded. Results: We observed an increased H-ferritin expression in the skin samples of AOSD patients, when compared with HC (p<0.001). On the contrary, no differences were observed for L-ferritin when compared to HC. Furthermore, a significant increase of H-ferritin was detected when compared with L-ferritin in AOSD patients (p<0.001) and when compared with both H-ferritin and L-ferritin in HC (p<0.001; p<0.001). Furthermore, a positive correlation between H-ferritin and the Pouchot's score was observed (p<0.01). We also reported a positive correlation among the tissue expression of H-ferritin and both serum ferritin (p<0.05) and CRP (p<0.05). The double staining between the H-ferritin and CD68 showed an increased presence of macrophages expressing H-ferritin in the inflammatory infiltrate when compared with HC (p<0.001). In the same samples, we did not observe any co-localization between CD68 and L-ferritin. However, our analysis failed to show any positive correlation among the number of CD68+/H-ferritin+ in the skin and disease activity, serum ferritin and inflammatory markers. Conclusions: Our data show an imbalance between the production of L- and H-ferritin in the skin of AOSD patients, associated with a strong infiltrate of CD68+/H-ferritin+ cells in the same samples suggesting a possible pathogenic role. Furthermore, a correlation between the levels of H-ferritin in the skin of these patients and the disease activity was observed. References: Gerfaud-Valentin M, et al. (2014) Adult-onset Still's disease. Autoimmun Rev 13:708–22. Rosário C, et al (2013) The hyperferritinemic syndrome: macrophage activation syndrome, Still's disease, septic shock and catastrophic antiphospholipid syndrome. BMC Med 11:185. Recalcati S, et al (2008) New functions for an iron storage protein: the role of ferritin in immunity and autoimmunity. J Autoimmun 30:84–9. Disclosure of Interest: None declared